Persistent activity in human parietal cortex mediates perceptual choice repetition bias - Anne E. Urai; Tobias H. Donner (Nature Communications, 2022)
There is a well-known behavioral tendency to repeat past decisions, but the neural basis of this tendency remains unclear. Here the authors show that persistent activity in parietal cortex seems to play a key role in these idiosyncratic choice repetition biases.